Comunicação interpessoal e intercultural entre brasileiros e alemães: análise dos momentos de conflito - Carolina de Viterbo Lage (2013)
This dissertation investigates the conflict situations of two filmed and transcribed interactions between Brazilians and Germans, males and females. It analyzes the way of realization of the occurring conflicts from a linguistic level, regarding verbal elements (such as negative words,hedges and interjections) and non-verbal ones (such as intonation, gestures, facial expressions) as well from a relational level, regarding strategies that concern the harmony of interaction. The linguistic elements and relational strategies can mitigate or intensify the effects of conflicts. The preferences for the use of these elements and strategies rely on cultural influences as well as on other possible factors, like individual characteristics. The results reveal different styles according to the cultural background and sex of the participants, outlining German, Brazilian, male and female styles. German men for instance manifest acompetitive conflict style, with low use of mitigating elements, whereas Brazilian men reveal an avoiding style, with higher use of mitigating elements and strategies concerning the harmony of interaction. On the other side, Brazilian and German women manifest an integrative style, with concern for listening to different points of view and an even higher use of mitigating elements. These differences show that not only the nationality but also the gender of the participants can shape the way they express themselves and behave. Moreover, they show the importance of considering a broader view for the investigation of cultural tendencies, regarding the belonging to different cultural groups and individual characteristics.